Erkin gúres sport túrinde sport trenerovkasın rejelestiriw, sportshılardıń texnik-taktik tayarlıǵı - Dawletbaev, А; Bekmurzaev, А (SCIENCE and SOCIETY, 2023)
The article describes the concepts of sports planning in freestyle wrestling, selection of young athletes, technical and tactical training, orientation to freestyle wrestling, taking into account the anatomical features and physiological capabilities of athlets.
Keywords: sport; planning; selection; training of athletes; freestyle wrestling; physical exercises; result; development; success